Treatment of industrial effluents and assessment of their impact on the structure and function of microbial diversity in a unique Anoxic-Aerobic sequential batch reactor (AnASBR). (1st May 2020) - Jena, Jyotsnarani; Narwade, Nitin; Das, Trupti; Dhotre, Dhiraj; Sarkar, Ujjaini; Souche, Yogesh
Abstract: A novel Anoxic-Aerobic Process (AnAP) that eliminated the anaerobic process was optimized and operated for the simultaneous remediation of phosphate, nitrate, and chemical oxygen demand (COD) from industrial effluents. Two sequential batch reactors (SBR) with AnAP were established for the treatment of effluent from two industries; phosphate fertilizer (AnASBR_PPL) and dairy industry (AnASBR_DW). The adaptability of the bacterial consortium in the SBRs, dominated by denitrifying phosphate accumulating organisms (DNPAOs), facilitates the stable performance of AnAP for simultaneous nutrient and COD removal. Up to 90% and 80% of COD removal were achieved in AnASBR_PPL and AnASBR_DW, respectively. Nearly complete denitrification was observed along with phosphate removal accounted for 90% in both the reactors. Granulation of sludge has been widely reported in aerobic reactors; however, interestingly, in this study, partial granulation of the sludge was observed in both the AnASBRs which facilitated the microorganisms to uptake a minimal amount of phosphate and nitrate even under the aerobic condition. The underlying mechanism of DNPAOs and other associated microbes in the consortium were investigated for microbial diversity by 16S rDNA based targeted amplicon sequencing using the Illumina platform and imputed metagenomic analysis. The dominance of Betaproteobacteria, Alphaproteobacteria, Gammaproteobacteria, and Bacteroidia was observed in AnASBRs. At steady-state operation, the identity of the core community members remained largly stable, but their relative abundances changed considerably in both the reactors as a function of varying industrial effluent. However, population of few strains such as Lactobacteriales, Enterobacteriales changed drastically with respect to the influent, as these strains were predominat in AnASBR_DW but not present in AnASBR_PPL. The dominant strains were the vital contributor to the gene pool encoding for denitrification, dephosphatation, TCA cycle, glycolysis, EPS production, and polyhydroxyalkanoate (PHA) storage, etc. Few less abundant but persistent species were also detected as contributors to these functional groups. It unveiled the TCA cycle remains preferable over conventional glycolysis in both the SBR irrespective of carbon source. The new AnASBR was proved to be an efficient alternative system that is energy efficient with higher ease of operation for the treatment of different industrial effluents without fail. Graphical abstract: Image 1 Highlights: Unique anoxic-aerobic SBR removed nutrient and organics from industrial effluents. First systematic study of population, metabolism (putative) in anoxic-aerobic SBR. PAOs and DNPAOs coexists but DNPAOs was dominant in SBRs treatning different WW. Lactobacteriales, Enterobacteriales present in AnASBR_DW but not in AnASBR_PPL. Change in effluent (carbon source) didn't alter TCA cycle as the favoured pathway.